2016
DOI: 10.1007/s00264-016-3359-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two- and three-dimensional measurement of the Cobb angle in scoliosis

Abstract: Purpose The Cobb angle as an objective measure is used to determine the progression of deformity, and is the basis in the planning of conservative and surgical treatment. However, studies have shown that the Cobb angle has two limitations: an inter-and intraobserver variability of the measurement is approximately 3-5 degrees, and high variability regarding the definition of the end vertebra. Scoliosis is a three-dimensional (3D) pathology, and 3D pathologies cannot be completely assessed by two-dimensional (2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 21 publications
2
36
0
Order By: Relevance
“…Firstly, Cobb angle is a two-dimensional measurement of a three-dimensional condition [ 48 ]. A measurement alone does not tell the entire story of a scoliotic spine.…”
Section: Pattern-specific Scoliosis Rehabilitation (Pssr)mentioning
confidence: 99%
“…Firstly, Cobb angle is a two-dimensional measurement of a three-dimensional condition [ 48 ]. A measurement alone does not tell the entire story of a scoliotic spine.…”
Section: Pattern-specific Scoliosis Rehabilitation (Pssr)mentioning
confidence: 99%
“…Previous studies have compared the performance of EOS with CT in the measurement of scoliotic curves, and most studies reported an excellent agreement between EOS and CT in measuring Cobb angle and confirmed EOS to be a reliable and accurate imaging acquisition method for scoliosis examination [22] , [23] . It is suggested that the biplanar X-ray sources and detectors of EOS system translate simultaneously along superoinferior direction; thus, the images produced do not have geometrical magnification, contrary to conventional projection imaging systems [24] .…”
Section: Discussionmentioning
confidence: 92%
“…11,[20][21][22][23][24] According to previous studies, the sagittal Cobb angle is also an important index used to evaluate the spine sagittal balance. 8,[25][26][27] In this study, for the single thoracolumbar vertebra fracture, we rede ned the sagittal Cobb angle of a single fractured vertebra as the sagittal Cobb* angle, and its measurement method. Our study rst measured the sagittal Cobb* angle of each segment of the normal thoracolumbar segment.…”
Section: Discussionmentioning
confidence: 99%